PELATIHAN PERANCANGAN PRODUK AKSESORIS FESYEN DI PENGRAJIN KAMPUNG PEUSAR, BINONG DENGAN PENDEKATAN CO-DESIGN - Devanny Gumulya (Jurnal Sinergitas PKM & CSR, 2017)
AbstractCollaborative design known as co-design is a design method that enables many stakeholders (designer, manufacturer, and users) to collaborate each other. This paper tries to study how the co-design method is applied to a commutiy service design project collaborating product design student 2013 batch collaborating with Peusar Artisans Community. From the study can be suggested that this methodology is fit to design process on the stage of discover and develop, through interview, forum group discussion and collaborative workshop to reduce the social culture background differences. Means of communication proven effective to be used in co-design are drawing and product sample. This method is proven to be very helpful for product design student because, it obliged the student to interact directly with the artisans, more empathy can yield better design outcome. Keywords: Co-design, designing, product design